IMPLEMENTASI KONSEP DASAR BIMBINGAN DAN KONSELING DALAM MENINGKATKAN PENGEMBANGAN PESERTA DIDIK DI SD GMIT 023 RUILAK KELURAHAN WALAI BARAT KECAMATAN TELUK MUTIARA KABUPATEN ALOR - Nurlaila B Arsyad; Silpa B. Fanau, Jefri Moban, Yessy Mata, Petrus Mau Tellu Dony, Nehemia Fanpada (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the basic concepts of guidance and counseling and their implementation as an effort to develop students at SD GMIT 023 Ruilak. Guidance and counseling are important processes in helping students overcome personal, social, and academic problems so as to improve their well-being and quality of learning. The research method used is a qualitative study with a descriptive approach, involving observation, interviews, and documentation at SD GMIT 023 Ruilak. The results of the study indicate that the implementation of the basic concepts of guidance and counseling effectively can support the development of character, emotional, and social students. This finding emphasizes the importance of the role of counselor teachers and the implementation of guidance programs in creating a school environment that supports the overall development of students.